Dynamic modelling of flexible link aerator with embedded holes to generate dissolved oxygen in tiger prawn pond - Zulkipli, Nazatul Erma (2015)
In the aquaculture industry, aerators are used to increase the level of dissolved oxygen in water by mixing the water in order to ensure that the oxygen content is uniformly distributed throughout the pond. This aerator uses a new concept by using flexible link by implementing embedded holes in its design in. The purpose of adding holes in the design is to achieve higher dissolved oxygen level. This research consists on developing a new mathematical model by modification of the Finite Difference Method to suit the irregular boundary of the new design of flexible link aerator. The simulation is done using Matlab SIMULINK and three voltages are chosen to be the input voltage which are 6V, 9V and 12V while the percentage of immerse level were set at 100%, 75%, 50% and 25%. The best result of dissolved oxygen level was achieved by running the simulation at 12V and 25% of immerse level using the 65cm length of PVC link .The simulation of this flexible link was able to oxygen up to 9.65 mg/L with the average Standard Oxygen Transfer Efficiency 2.15 kgO2/kWhr.